2001
DOI: 10.1677/jme.0.0260193
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and hormonal regulation of type II DNA topoisomerase in rat testis

Abstract: Type II DNA topoisomerase (topo II) is required for diverse biological functions including DNA replication, maintenance of genome stability, chromosome segregation and chromosome condensation. While the identity of topo II in rodent testis has been established, the regulation of topo II expression during the development of the postnatal testis and gametogenesis is unclear. Here, we report that rat testis topo II is developmentally and hormonally regulated. Topo II mRNA levels peaked prior to the onset of puber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…In rodents, it has recently been demonstrated that testosterone increased expression of DNA topoisomerase II, the key enzyme that nicks and ligates DNA molecules during the histone-to-protamine transition process (Marcon & Boissonneault 2004). Moreover, testosterone is required for the maintenance of topoisomerase II expression during spermatogenesis (McPherson & Longo 1993, Bakshi et al 2001. A Swedish study on young males reported a weak, negative association, between CB-153 and free testosterone levels (Richthoff et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, it has recently been demonstrated that testosterone increased expression of DNA topoisomerase II, the key enzyme that nicks and ligates DNA molecules during the histone-to-protamine transition process (Marcon & Boissonneault 2004). Moreover, testosterone is required for the maintenance of topoisomerase II expression during spermatogenesis (McPherson & Longo 1993, Bakshi et al 2001. A Swedish study on young males reported a weak, negative association, between CB-153 and free testosterone levels (Richthoff et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that topoisomerase II may be responsible for the strand breakage and ligation steps in both the rat and chicken models [8,30,38]. In contrast, Bakshi et al have shown that topoisomerase II was not expressed in rat spermatids [1]. Hence, the topology-modifying enzymes involved in the process remains to be identified.…”
Section: Elimination Of Supercoiling By Dna Strand Breaksmentioning
confidence: 99%
“…Topo2a and Stmn1 serve as substrates for Aurkb during mitosis [21, 22] and promote chromosome segregation during cell proliferation [23, 24]; activities that may have relevance to prostatic epithelial cell hyperplasia in the lateral lobe of aging rats. In the lateral lobe of 4 month old rats, Topo2a immunostaining was localized to nuclei of widely dispersed luminal epithelial cells as well as some basal epithelial cells and stromal cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although we do not know the phosphorylation status of Stmn1 in the lateral lobe, upregulation and differential phosphorylation of human Stmn1 have been observed in prostate cancer specimens and cell lines [44]. Interestingly, Topo2a, Aurkb, and Stmn1 are co-expressed in proliferating germ cells of the testis [24, 33, 41, 45]. Given their key roles in proper cell division, Stmn1, Aurkb, and Topo2a serve as robust markers of cell proliferation in the Brown Norway rat lateral prostate and if overexpressed could lead to the accumulation of chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%